Respuesta :

Answer: -16d³ + 3d² - 3d + 2

Step-by-step explanation:

Given expression

(4d - 6d³ + 3d²) - (10d³ + 7d - 2)

Expand parentheses

(REMEMBER to change [+, -] signs when there is a [-] sign in before)

=4d - 6d³ + 3d² - 10d³ - 7d + 2

Put like terms together

=-6d³ - 10d³ + 3d² + 4d - 7d + 2

Combine like terms

=(-6d³ - 10d³) + 3d² + (4d - 7d) + 2

=[tex]\boxed{-16d^3+3d^2-3d+2}[/tex]

Hope this helps!! :)

Please let me know if you have any questions

Answer:

-16d³ + 3d² -3d + 2

Step-by-step explanation:

(4d−6d³+3d²) − (10d³+7d−2) =

-6d³ - 10d³ + 3d² + 4d - 7d + 2 =

-16d³ + 3d² -3d + 2

ACCESS MORE